Prevalence of monogamy at the level of flowers in plants - Kamaljit S. Bawa; Namratha Tiwari; K. Nagaraju Shivaprakash (Proceedings of the National Academy of Sciences, 2025)
Different types of genomic conflicts are possible in plants with multiovulate ovaries that produce multiseeded fruits: between the maternal plant and its offspring, among developing seeds, between paternal and maternal genomes over seed development, and among paternal parents if different parents sire seeds within an ovary. We tested the hypothesis that such conflicts in multiseeded fruits can be reduced if seeds are sired by a single pollen parent. We conducted a meta-analysis of paternity in 63 species across diverse plant families to assess paternity within fruits. Our results reveal that almost 50% of flowering plant species with multiseeded fruits have a single pollen parent. Our results question the prevailing notion that multiple paternity of seeds within fruits is widespread, especially when, in addition to single paternity in multiseeded fruits, a large number of species have single-seeded fruits. We provide insights into the role of sibling rivalry and kin selection in driving genetic relatedness of seeds within fruits. Equally important, the observation of monogamy at the level of flowers is in line with the mating patterns observed in animals.